TWO SORTS OF BARE NOUNS IN BRAZILIAN PORTUGUESE - Oliveira, Roberta Pires de; Rothstein, Susan (Revista da ABRALIN, 2011)
It is a consensus in the literature that the so called Bare Singular (BS, from now on) in Brazilian Portuguese (BrP) is not semantically singular (Munn & Schmitt 1999, a.o.), but a number neutral count noun. In this paper, we explore the hypothesis that it is not a count noun. We reach such a conclusion by comparing the bare singular with both the bare mass noun and the bare plural count noun. We show that the behavior of the bare singular in BrP does not parallel that of the bare plural, but strongly parallels that of the bare mass noun. Based on such facts we propose that there are just two sorts of bare nouns in BrP: Bare Mass and Bare Plural. The Bare Mass denotes either the kind or a mass predicate, whereas the Bare Plural always denotes a plural predicate. These different semantics explain their different behavior. As conclusion, we show some unexpected results from our approach. The outline of the paper is as follows. We begin by showing that the prima facie arguments against treating bare singulars as mass nouns are not valid. Our claims are based on the fact that the literature has compared bare singular nouns with non-atomic mass nouns, and has shown that they behave differently with respect to the relevant tests. However, comparing bare singulars with naturally atomic mass nouns such as mobília ‘furniture’ gives different results. We then show, in section 2, that the bare singular displays the same distributional restrictions as the bare mass noun both in episodic and generic contexts, a fact that, as far as we know, has gone unnoticed in the literature. This strengthens the case for treating them alike. In section 3 we give a semantics for mass nouns and count nouns in the framework of Rothstein 2010a, b which allows for a unified analysis of bare singulars and mass terms, that differs from that attributed to the bare plural. In section 4, we explain the data from earlier sections in the light of the analysis, and propose a semantics for bare plurals which explains their behavior in BrP. Finally, we also show that our account predicts that so called ‘bare singulars’ can occur with mass determiners, and we give arguments to show that this prediction is correct. Moreover its behavior in comparative contexts also supports our hypothesis that it is a mass.